State responsibility and new trends in the privatization of warfare - Renz, Frauke (Edward Elgar Publishing, 2020)
"Contracts with private military and security companies are a reality of modern conflicts. This discerning book provides nuanced insights into the international legal implications of these contracts, and establishes an in-depth understanding of the impacts for contracting states, home states and territorial states under the current state responsibility regime. Focussing on the Articles on State Responsibility (ASR) the author considers under which conditions states are, or should be, responsible for the acts of private contractors given new trends towards remote warfare involving drones and increasingly autonomous weapon systems. Rigorous academic research and case studies, combined with insights from numerous interviews with practitioners, serve to highlight the challenges to applying the ASR. These challenges range from the relativity of key concepts of attribution to the issue of when reliance on private contractors becomes a violation of the principle of distinction under International Humanitarian Law and also illustrate where the current state responsibility regime needs to be modified to adequately address evolutions in warfare. This astute and incisive book will prove a key resource for legal scholars and theorists with an interest in public international law, IHL and IHRL. Government officials, practitioners and think tanks engaged in compliance matters and new trends in warfare will also benefit from this work's pragmatic approach"--